2017
DOI: 10.1002/mrm.26679
|View full text |Cite
|
Sign up to set email alerts
|

A pneumatic phantom for mimicking respiration‐induced artifacts in spinal MRI

Abstract: Purpose: To design a phantom capable of mimicking human respiration to serve as a testing platform for correction of the static and time-evolving magnetic field distortions typically encountered in MRI of the spinal cord. Methods: An inflation system to mimic the air variation of the human lungs was constructed. The inflation system was linked to a phantom containing synthetic lungs and an ex vivo human spine. The relationship between air pressure and phantom lung volume was evaluated via imaging experiment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The ME-GRE sequence is feasible 95 but might require additional averaging 96 , and/or the use of navigator echoes to compensate for respiratory-related ghosting. Protocol optimization could be aided by the use of advanced spinal cord phantoms made of "tissue-like" materials that mimic respiration-related dynamic changes in the B 0 field, such as the one proposed by De Tillieux et al 97 .…”
Section: Thoraco-lumbar Cordmentioning
confidence: 99%
“…The ME-GRE sequence is feasible 95 but might require additional averaging 96 , and/or the use of navigator echoes to compensate for respiratory-related ghosting. Protocol optimization could be aided by the use of advanced spinal cord phantoms made of "tissue-like" materials that mimic respiration-related dynamic changes in the B 0 field, such as the one proposed by De Tillieux et al 97 .…”
Section: Thoraco-lumbar Cordmentioning
confidence: 99%
“…In this study, the effect of respiration physiological noise was strongly observed in the cardiac noisecorrected datasets, and ROC analysis demonstrated that the sensitivity and specificity of the respiration effect correction were increased. This result can be ex- The graphs show how the type of correction step influences the number of active voxels in the CSF areas plained by considering the bulk magnetic susceptibility changes and the associated B0 shifts in the spinal cord by respiration and the changes in the volume of lungs (Tillieux et al, 2018;Verma, 2014). B0 field shifting is reported to affect the pre-processing and GLM analysis of the spinal cord fMRI data (Durand, van de Moortele, Pachot-Clouard, & Le Bihan, 2001;Parkes, Fulcher, Yu, & Fornitod, 2018;Raj, Anderson, & Gore, 2001;Yeo, Fessler, & Kim, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Several sources of physiological noises have been described in the fMRI literature, including those associated with cardiac and respiratory processes which were recognized as the most significant ones (Brooks, 2014;Fratini et al, 2014;Kong et al, 2014). Spinal cord in thoracolumbar is close to the lungs and the diaphragm, that influence cerebrospinal fluid-filled spaces and cause changes in the susceptibility due to the changes in the amount of air in the lung (Tillieux et al, 2018;Verma & Cohen-Adad, 2014). Cardiac physiological noise is produced as a result of changes in Cerebral Blood Flow (CBF), Cerebral Blood Volume (CBV), arterial pulsatility, and effect of those on the CSF flow (Fratini et al, 2014;Parrish, Gitelman, LaBar, & Mesulam, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A very simple phantom, which can be assembled by mostly 3D printed parts, is the open‐source NIST phantom 119,229 . Phantoms for very specific applications are also available to assess image distortions, for example, in image‐guided interventions such as MR‐guided radiation therapy, 115,230 3D printed phantoms to evaluate contrast agent solutions, 112,231 for perfusion imaging, 100 or pneumatic phantoms to mimic respiration‐induced artifacts 124,232 . A very useful tool to calculate gel ingredients for sucrose and polyvinylpyrrolidone (PVP)‐based phantoms with a targeted permittivity and electric conductivity is available online 233–235 .…”
Section: Open‐source Mr Scannersmentioning
confidence: 99%